Picture and Picture Learning Strategy to Increase Fiqh Learning Activity and Outcomes - Fransistyawan, Rioga; Fakhriyendi Rizkullah, Muhammad; Ra'uf, Muhammad; Sapto Wahono, Suparwoto (Innovative: Journal Of Social Science Research, 2025)
This study aims to improve the activeness and learning outcomes of class II students in Fiqh subjects through the application of the Picture and Picture learning strategy. The background of the study shows low learning outcomes in Fiqh subjects, where 75% of students get scores below the KKM. This study is a collaborative Classroom Action Research (CAR) carried out in two cycles consisting of: Planning, Implementation, Observation, and Reflection. Data collection techniques include observation and learning outcome tests. The results of the study showed that the application of the Picture and Picture strategy was able to increase student activity from 75% to 88% and increase the completeness of learning outcomes from 56% to 81%. Thus, this strategy is effective in improving the quality of Fiqh learning. Based on the discussion above, the researcher provides suggestions: 1) for teachers to have learning innovations by implementing learning models that are considered to be able to help the learning process and to prepare teaching materials well and completely. 2) for further researchers who apply the Picture and Picture Learning Model to be able to develop with different variations such as different variables, different indicators, or different subjects